(untitled) (Review of Croatian History, 2021)
The largest and most luxurious passenger ship in the Adriatic was the steamship “Queen Mary”, that initially held constant 12-days line from Sušak, via Split and Dubrovnik to Greece. Later, that line was extended to Palestine and Egypt, and has attracted the attention of members of the Zagreb elite. Among the first ones who have travelled that line, from September 13th until October 7th, 1933, was the prominent Zagreb’s entrepreneurial family Deutsch-Maceljski. Their experience and atmosphere from the cruise and places they visited were recorded by the film camera. They recorded footage and descriptions of Istanbul, the Bosphorus, Rhodes, Beirut, Lebanon and Damascus, and the most fascinating images and descriptions were the family visits to Jaffa, Jerusalem, the Dead Sea, Bethlehem, Tel Aviv and Cairo. In this article, we will analyze this rare film that has been preserved in the Cinematheque of the Croatian State Archives in Zagreb.